UKURAN PERUSAHAAN DAN FEE AUDIT SEBAGAI PENENTU KUALITAS AUDIT: STUDI KASUS PADA PERUSAHAAN SEKTOR PROPERTY DAN REAL ESTATE YANG TERDAFTAR DI BURSA EFEK INDONESIA 2021-2023 - Aditya Pradana; Vera Amalia; Liona Efrina; Yenni Affriyanti (Jurnal Akuntansi Kompetif, 2026)
This study aims to examine the influence of company size and audit fees as determinants of audit quality. The population in this study were property and real estate companies listed on the Indonesia Stock Exchange (IDX) for the 2021-2023 period. The sampling method used was purposive sampling. The sample size in this study was 47 companies over a three-year period, resulting in a total sample of 141. The data analysis methods used to test the hypotheses were descriptive statistics and logistic regression analysis using SPSS software. The results of this study indicate that company size and audit fees influence audit quality. Keywords: Firm Size, Audit Fee, Audit Quality